An Evaluation of E-Learning Implementation During Covid-19 Pandemic in Elementary School - Masfuah, Siti; Fakhriyah, Fina; Hakim, Muhammad Malik (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to evaluate the implementation of online learning at SD 3 Wergu Wetan. This evaluative research uses the Stake model from the planning, implementation stages, and which is then linked to the online learning implementation guide from the Ministry of Education and Culture. Subjects were taken purposively consisting of principals, teachers, and students, as well as parents as measured by interviews, documentation, and observation. Data were analyzed descriptively qualitatively. The results showed that in planning, the teacher emphasized the achievement of the main indicators, reading, writing, and arithmetic skills, using student worksheets. The implementation aspect, learning process uses WhatsApp, YouTube, and study groups. Parents and internet connections are critical success factors for online learning. Teachers need the training to create their own media. In the output aspect, the average score of students is good but students’ abilities are not in accordance with the results achieved because the exam is done at home so that an online assessment is needed that students can do independently. Implementation of online learning has been going quite well and is included in the B category.